Multi-functionality and land use dynamics in a peri-urban environment influenced by wastewater irrigation - Jampani, Mahesh; Amerasinghe, Priyanie H.; Liedl, R.; Locher-Krause, K.; Hulsmann, S. (Elsevier, 2020)
Peri-urban areas are characterized by multifunctional land-use patterns forming a mosaic of built-up and agricultural areas. They are critical for providing food and other agricultural products, livelihood opportunities and multiple ecosystem services, which makes them transformative where urban and rural spaces blend. We analyzed land use changes in a peri-urban micro-watershed in Southern India by using Google Earth data to understand the micro-level spatio-temporal dynamics. This study aims at understanding the peri-urban agriculture and landscape changes as related to the change in use of wastewater and groundwater for irrigation. The temporal dynamics of peri-urban system including the changes in built-up, paragrass, paddy rice and vegetable cultivation, groundwater and wastewater irrigated areas in the watershed were evaluated. The detected changes indicate that, as a consequence of urban pressures, agricultural landscapes are being converted into built-up areas and, at the same time, former barren land is converted to agricultural plots. The mapped land use data are used in landscape change modelling for predicting the peri-urban agricultural dynamics and the driving factors in the watershed. Combined with the mapping and modelling approaches for land use change analysis, our results form the basis for integrated resources management in the wastewater influenced peri-urban systems.